Relationship between Protein kinase C and derepression of different enzymes - Salgado, A. C. P. (2002)
The PKC1 gene in the yeast Saccharomyces cerevisiae encodes for protein kinase C which is known to control a MAP kinase cascade consisting of different kinases: Bck1, Mkk1 and Mkk2, and Mpk1. This cascade affects the cell wall integrity but the phenotype of pkc1∆ mutants suggests additional targets that have not yet been identified [1]. The pkc1∆ mutant, as opposed to other mutants in the MAP kinase cascade, displays defects in the control of carbon metabolism. One of them occurs in the derepression of SUC2 gene after exhaustion of glucose from the medium suggesting an involvement of Pkc1p in the derepression process that is not shared by the downstream MAP kinase cascade. In this work, we demonstrate that Pkc1p is required for the increase of the activity of enzymatic systems during derepression process. We observed that Pkc1p is involved in the derepression of invertase and alcohol dehydrogenase activities. On the other hand, it seems not to be necessary for the derepression of the enzymes of the GAL system. Our results suggest that Pkc1p is acting through the main glucose repression pathway since introduction of an additional mutation in the PKC1 gene in yeast strains already presenting mutations in the HXKII or MIG1 genes does not interfere with the typical derepressed phenotype observed in these single mutants. Moreover, our data indicate that Pkc1p participates in this process through the control of the cellular localization of the Mig1 transcriptional factor.